PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA PESERTA DIDIK KELAS V SD NEGERI PALEMBANG - Maria, Maria (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
The purpose of this research is to improve mathematics learning outcomes through the STAD type cooperative learning model for fifth grade students at SD Negeri 36 Palembang. This research was conducted by the author at SD Negeri 36 Palembang. In accordance with this research, the authors conducted for 3 months, starting from August to November 2019. The subjects of the research were fifth grade students at SD Negeri 36 Palembang which consisted of 23 students plus a collaborator as an observer in learning activities. Through the results of this research, it is shown that the learning process with the STAD type cooperative learning model can improve the learning outcomes of fifth grade Mathematics at SD Negeri 36 Palembang. This can be seen from the higher mathematics learning outcomes of students on the material that has been conveyed by the teacher so far. Mastery learning increased from pre-cycle, cycle I to cycle II, respectively 26.09%, 65.22% and 91.30%. In cycle II, students' learning mastery classically has been achieved and has experienced a very good increase.